1968
DOI: 10.1152/ajplegacy.1968.215.2.389
|View full text |Cite
|
Sign up to set email alerts
|

Role of cerebral arterial blood in the regulation of brain temperature in the monkey

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
143
1
1

Year Published

1970
1970
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(165 citation statements)
references
References 11 publications
20
143
1
1
Order By: Relevance
“…Proteins and amino acids may have a pyrogen-like influence and reset the set point in the awake state (16,17), possibly via a second messenger. Body oxidative metabolism keeps the body core temperature constant and prevents hypothermia in the awake state (18). However, anesthesia may suppress this thermic control.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins and amino acids may have a pyrogen-like influence and reset the set point in the awake state (16,17), possibly via a second messenger. Body oxidative metabolism keeps the body core temperature constant and prevents hypothermia in the awake state (18). However, anesthesia may suppress this thermic control.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 This may be explained by the high metabolic activity of cerebral tissue with considerable production of heat. 37 Another possibility is that in the early stages of infarct formation, a decrease in cerebral blood flow may result in a decreased capacity for the blood to carry off heat generated by local cerebral metabolism. In animal studies, it was reported that toxicity from moderate hypothermia increases as the temperature is further decreased and as the duration of hypothermia is increased.…”
Section: Discussionmentioning
confidence: 99%
“…Although administration of low doses of IL-1 and IL-1RA can influence outcome from experimental cerebral ischemia independently of rectal temperature (10,11), core body temperature may not be representative of temperature in critical ischemic areas of the brain. Brain temperature in health correlates well with body temperature (12,13) but there is good evidence that brain temperature dissociates from body temperature during ischemia. Ischemic brain temperature falls by 1-2°C relative to rectal temperature in rodent models of focal cerebral ischemia with little change in the temperature of the nonischemic hemisphere (14,15).…”
mentioning
confidence: 99%